2011
DOI: 10.1007/s00784-011-0513-3
|View full text |Cite
|
Sign up to set email alerts
|

Survival of atraumatic restorative treatment (ART) sealants and restorations: a meta-analysis

Abstract: The purpose of this study is to perform a systematic investigation plus meta-analysis into survival of atraumatic restorative treatment (ART) sealants and restorations using high-viscosity glass ionomers and to compare the results with those from the 2005 ART meta-analysis. Until February 2010, four databases were searched. Two hundred four publications were found, and 66 reported on ART restorations or sealant survival. Based on five exclusion criteria, two independent reviewers selected the 29 publications t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
141
3
14

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(166 citation statements)
references
References 60 publications
8
141
3
14
Order By: Relevance
“…They investigated ART sealants after six years and observed that cavitation due to caries occurred very rarely in ART sealed teeth even when the sealant was partially or totally missing. A recent meta-analysis concluded that although the survival rate of ART sealants with high viscosity glass ionomer after 3 years was 72%, the result for dentine lesion-free sealed pits and fissures was 97% after the same period (Amorim et al 2012). Accordingly, a preventive effect of high viscosity glass ionomer sealants was observed even in re-exposed pits and fissures surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…They investigated ART sealants after six years and observed that cavitation due to caries occurred very rarely in ART sealed teeth even when the sealant was partially or totally missing. A recent meta-analysis concluded that although the survival rate of ART sealants with high viscosity glass ionomer after 3 years was 72%, the result for dentine lesion-free sealed pits and fissures was 97% after the same period (Amorim et al 2012). Accordingly, a preventive effect of high viscosity glass ionomer sealants was observed even in re-exposed pits and fissures surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Dit type restauratiemateriaal schoot echter tekort voor meervlaksrestauraties in tijdelijke gebitselementen ( De Amorim et al, 2012). Dit leek te wijten aan het restauratiemateriaal zelf en mogelijk aan de vaardigheid en zorgvuldigheid van de mondzorgverleners.…”
Section: Vaardigheid En Zorgvuldigheid Mondzorgverlenerunclassified
“…3) ( De Amorim et al, 2012). Ontegenzeggelijke voordelen zijn dat het onder klinische omstandigheden eigenschappen heeft die vergelijkbaar zijn met die van dentine en dat het gunstig reageert op de heersende temperatuur en vochtige omstandigheden in de mond (McCabe et al, 2009).…”
Section: Conventioneel Glasionomeercementunclassified
“…Specially designed for ART, the high-viscosity GICs have a relatively slow curing and improved mechanical properties compared to low and medium viscosity cements, which has resulted in increased survival of restorations 13 . Recent systematic reviews have shown that the longevity of ART restorations with high-viscosity GICs is similar to the gold standard treatment with amalgam 12,[14][15][16] .…”
Section: Introductionmentioning
confidence: 96%